(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-98-108 We consider the category of “paschality”, introduced into Russian literature studies by Ivan Esaulov, in Anton Chekhov’s tale “In the Ravine”. In Russia, Easter is celebrated more solemnly than Christmas. According to I. Esaulov, this makes people give greater importance to life in Heaven and makes them ready to suffer and die in order to receive it. We recognize that the category of “paschality” can be fruitful for literature studies and, in particular, for the interpretation of Chekhov’s tale. Yet, we propose to amend it. We disagree with I. Esaulov’s opinion that giving a key importance to Easter distinguishes Russian Orthodoxy from the Christian West. But, first and foremost, we think that the paschal spirituality of the New Testament should not be juxtaposed neither to the Pascha (Passover, Exodus) of the Hebrew Bible, nor to the crucial role the New Testament gives to the Christmas mystery of the Incarnation. Instead, the paschal mystery should rather be seen as the continuation and fulfillment of both. This kind of “paschality” complements the social criticism of the tale “In the Ravine” and gives it a deeper sense. The horror described in “In the Ravine”, which reaches its culmination in the little child’s murder, is both exacerbated and softened by allusions to Christ’s birth and to Our Lady. Besides, due to references to the salvation of little Moses and the newborn Jesus, even ex negativo the tale alludes to Lipa’s and her fellow workers’ future salvation and liberation. Key words: Anton Chekhov, Ivan Esaulov, social criticism, Easter, Passover, Exodus, Christmas